Tokens in Classical Athens and Beyond - Gkikaki, M.E (Liverpool University Press, 2023)
A selection of essays on symbola, as the tokens of Classical Athens were called, bringing together scholars of various disciplines and professional categories (numismatists, historians, museum curators) that intends to reshape our knowledge on the roles these objects played in the Athenian Democracy. This is a series of case studies which aspires to test old theories and probe new assumptions. The first section explores the extent to which our knowledge has evolved since symbola were first distinguished from coins. Four essays demonstrate how tokens, as material manifestations of particular institutions, contributed to the formation of civic and political identity in the city-state of Athens and the roles they played in ensuring legal and political equality. The second section of the volume on new finds aims to develop expertise in studying tokens and increase relevant knowledge. Finally, a third section contains comparative studies from Sicily, Jerusalem and Ephesos, aiming to adopt a comparative methodology for a better understanding of the characteristics and roles of tokens from across the ancient Mediterranean.